The Implemntation oF The CSE-UCLA Evaluation Model in Assesing The Effectiveness oF The Entrepeneuship Program atT SMA IT ABU BAKAR - Putri, Musdalipah; suwardi, Suwardi (JIEM (Journal of Islamic Education Management), 2024)
The entrepreneurship program at SMA IT Abu Bakar Yogyakarta is designed to equip students with entrepreneurial skills grounded in Islamic values while supporting their readiness to face the challenges of the business world. This study aims to evaluate the program's effectiveness using the CSE-UCLA (Center for the Study of Evaluation at UCLA) model, which comprises four stages: Need Assessment, Program Planning, Formative Evaluation, and Summative Evaluation. The research employs a qualitative approach and case study methodology to collect in-depth data. Data collection methods include interviews, field observations, and document analysis involving various stakeholders, such as students, teachers, and program administrators. During the Need Assessment stage, the program successfully identified students' needs aligned with the objectives of entrepreneurship education. Program Planning demonstrated that the program's design effectively supports the development of students' entrepreneurial skills. Formative Evaluation revealed regular monitoring efforts to ensure the program's implementation proceeded as planned. Summative Evaluation showed an improvement in students' skills after participating in the program, as well as providing practical experiences relevant to the business world. The findings indicate that applying the CSE-UCLA evaluation model offers a comprehensive understanding of the entrepreneurship program's effectiveness. The program can be further developed by strengthening planning, implementation, and evaluation to optimize its benefits for students and the school. This research contributes significantly to Islamic educational institutions in designing entrepreneurship programs based on measurable and sustainable evaluations.